Generation of a Gaussia luciferase-expressing endotheliotropic cytomegalovirus for screening approaches and mutant analyses - Falk, Jessica J.; Sampaio, Kerstin Laib; Stegmann, Cora; Lieber, Diana; Kropff, Barbara; Mach, Michael; Sinzger, Christian (Journal of Virological Methods, 2016)
For many questions in human cytomegalovirus (HCMV) research, assays are desired that allow robust and fast quantification of infection efficiencies under high-throughput conditions. The secreted Gaussia luciferase has been demonstrated as a suitable reporter in the context of a fibroblast-adapted HCMV strain, which however is greatly restricted in the number of cell types to which it can be applied. We inserted the Gaussia luciferase expression cassette into the BAC-cloned virus strain TB40-BAC4, which displays the natural broad cell tropism of HCMV and hence allows application to screening approaches in a variety of cell types including fibroblasts, epithelial, and endothelial cells. Here, we applied the reporter virus TB40-BAC4-IE-GLuc to identify mouse hybridoma clones that preferentially neutralize infection of endothelial cells. In addition, as the Gaussia luciferase is secreted into culture supernatants from infected cells it allows kinetic analyses in living cultures. This can speed up and facilitate phenotypic characterization of BAC-cloned mutants. For example, we analyzed a UL74 stop-mutant of TB40-BAC4-IE-GLuc immediately after reconstitution in transfected cultures and found the increase of luciferase delayed and reduced as compared to wild type. Phenotypic monitoring directly in transfected cultures can minimize the risk of compensating mutations that might occur with extended passaging.
EVALuna2:8325